Metronomic chemotherapy - Maiti, Rituparna (Medknow Publications & Media Pvt Ltd, 2014)
Toxic effects and chemoresistance are major hurdles in chemotherapy and to avoid these problems caused by traditional chemotherapeutic regimens, a new modality of drug administration called “metronomic chemotherapy” has emerged. Such regimen involves the frequent administration of conventional chemotherapeutic agents at very low doses to target activated endothelial cells in tumors, the advantages of which include minimal adverse effects and a rare chance of developing acquired drug resistance. Previously it was thought that they act by targeting angiogenesis, but recently additional mechanisms have been discovered which has established metronomic chemotherapy as a type of multi-targeted therapy. The knowledge gained from the preclinical studies of metronomic chemotherapy, along with clinical experience, will help to design better therapeutic protocols against cancer. Detailed pharmacogenomic and pharmacoproteomic studies on tumor endothelial cells and large multi-centered clinical trials, integrating bio-marker analyzes, are needed to investigate and validate the best treatment combinations for each tumor type and patient population.